DNA methylation down‐regulates integrin β4 expression in asthmatic airway epithelial cells. Issue 10 (17th July 2020) - Wu, Mengping; Yang, Yu; Yuan, Lin; Yang, Ming; Wang, Leyuan; Du, Xizi; Qin, Ling; Wu, Shuangyan; Xiang, Yang; Qu, Xiangping; Liu, Huijun; Qin, Xiaoqun; et al.
Abstract: Background: Integrin β4 (ITGB4) is a hemi‐desmosome protein which is downregulated in the airway epithelial cells of asthma patients. The proximal promoters and exons of ITGB4 contain CpG islands or multiple CpG sites both in human and mice, which indicated the possible methylation regulation of ITGB4 in airway epithelial cells. Objective: We sought to unveil that DNA methylation regulates the decreased ITGB4 during the pathogenesis of asthma. Methods: Mice were exposed to house dust mite (HDM) extracts to construct an asthma model. 5‐Aza‐2'‐deoxycytidine (5‐AZA) or dexamethasone (DEX) were added in the last two weeks. Besides, the primary human bronchial epithelial (HBE) cells were incubated for the detection of ITGB4 expression and methylation status after HDM stress. Furthermore, DNA methylation of ITGB4 in peripheral blood was measured in asthma patients. Logistic regression was employed to evaluate the association between methylation sites and asthma patients' ages in the control of potential confounders. Moreover, the correlations between differentially methylated sites (DMSs) and clinical parameters in asthma patients were assessed. Finally, the ability of candidate DMSs to predict asthma was evaluated by receiver operating characteristic (ROC) analysis and principal component analysis (PCA). Results: We found that in HDM‐stressed asthma model, DNA methylation regulated the reduced ITGB4 expression in airway epithelial cells. Moreover, alteration in the specific CpG sites (chr17:73717720 and chr17:73717636) of ITGB4 may regulate ITGB4 expression and further may be associated with the clinically phenotypic of asthma. The specific DMSs of ITGB4 in peripheral blood can distinguish asthma patients from healthy controls (HCs) effectively. Conclusions and Clinical Relevance: This study confirmed that DNA methylation regulates the decreased expression of ITGB4 in the airway epithelial cells of asthma patients. These results supply some useful insights to the mechanism of the decreased ITGB4 in asthmatic airway epithelial and provide possible targets for early prediction and screening of asthma.